Suicide and external mortality pattern in a cohort of migrants from the former Soviet Union to Germany - Deckert, Andreas; Winkler, Volker; Meisinger, Christa; Heier, Margit; Becher, Heiko (Journal of psychiatric research, 2015)
Background - Mental health consequences of migration are manifold. Where some migrants experience migration as liberation from life threatening conditions, others suffer from hostility and social descent in the target country. This study investigates deaths due to external causes, suicides, and events of undetermined intent in German repatriates from the Former Soviet Union. The relation between age at migration and suicide mortality is also explored. - Methods - A cohort of German repatriates who migrated between 1990 and 1999 was followed-up until 2010. Each individual accumulated time at risk, expressed in person years (PY). Standardized mortality ratios (SMR) were calculated, supplemented by subgroup analyses for age and calendar year strata, and immigration period. Multivariate Poisson models were used to investigate the influence of age, sex, calendar year, number of moves, and final move distance. - Results - A total of 6378 German repatriates (3031 men, 3347 women) accumulated 92 149 PY. Median age at immigration was 30 years in women and 27 years in men. Women's all-cause mortality was significantly lower (SMR = 0.85 [0.75; 0.97]). Men more often died from external causes (SMR = 1.58 [1.09; 2.23]), intentional self-harm (SMR = 1.68 [0.90; 2.88]), and events of undetermined intent such as poisoning by drugs (SMR = 8.07 [4.02; 14.44]). External cause mortality was significantly increased after 1995 (SMR = 1.87). In particular, men who migrated when they were 11-20 years old were at strongly increased risk of committing suicide (SMR = 3.84) or dying due to events of undetermined intent (SMR = 14.75). - Conclusion - The most endangered subgroup is men who migrated at teenage age. Protective factors such as strong family bounds formerly present in the FSU failed in Germany, the higher population density caused intense friction. The changes in the families' ethnical composition from mostly ethnic German members in the early 90s' towards predominantly Russian members around the turn of the millennium complicated integration. Setting-oriented prevention measures should consider the families' migration history, their link to culture and religion, and the different concepts of mental health.